Kinematic parameters for large trunk twist torque outputsduring the bar twist exercise - Takahashi, K.; Shinohara, H. (ISBS Proceedings Archive (Michigan), 2020)
This study aimed to clarify the kinematic characteristics for large trunk twist torque outputs during a bar twist exercise, focusing on the angle and angular velocity of the trunk twist.Twenty-one healthy male college athletes performed the bar twist exercise. Kinematic and kinetic data were recorded using the Vicon system (250 Hz) and two force platforms (1000 Hz). The participants were divided into two groups based on the maximal trunk twist torque of an individual compared to the mean value of the all participants. The results revealed that participants who had a large trunk twist torque output showed a large trunk twist angle against the direction of rotation and a large negative trunk twist angular velocity. Therefore, during bar twist training, a maximal trunk twist angle and a large negative angular velocity at the countermovement motion could be effective in obtaining large trunk twist torque.